A Novel Powder Metallurgy Technique for Introducing Synthetic Inclusions into Liquid Steel. (May 2019) - Smith, A; Tran, T; Ji, F; Tiekink, W; Abbel, G; Verdier, S
Abstract: Previous studies have shown that it is extremely problematic to add synthetic inclusions successfully into liquid steel for clean steel experiments. Small micro-particles encapsulated in a metallic parcel are difficult to pass through the melt-gas interface and inclusions tend to agglomerate then float up to the liquid surface. In this study, powder metallurgy is used to distribute cerium oxide particles of a known size from 1µm to 14µm within a small-scale steel ingot. Carbonyl iron powder has been mixed with 0.1 wt.% cerium oxide (CeO2 ) then sintered in an electrical furnace to produce sintered ingots of 500 grams. A series of induction furnace melting trials using a total of 400 grams of electrolytic iron and cerium oxide sintered ingot have been undertaken. The work has included extensive FE-SEM analysis using the INCA Feature ® to characterise synthetic cerium oxide inclusions from both the sintered ingots and trial ingots. The INCA Feature ® results showed that the size distribution and number of cerium oxide inclusions agreed well between the sintered ingot and trial ingot. The synthetic cerium oxide inclusions are homogeneously dispersed through the bottom, centre and top of the trial ingot with approximately 16 number counts/mm 2 . Analysis suggests that more than 95% of the cerium oxide from the sintered ingot has been distributed throughout the trial ingot. The work has also been upscaled from 400 grams up to 1.5 kg and has been successful. The method developed will be useful for further studies into steel cleanness of high value alloyed steels.